2022
DOI: 10.1186/s13002-021-00497-2
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical study on plants used to dye traditional costumes by the Baiku Yao nationality of China

Abstract: Background The Baiku Yao is a branch of the Yao nationality in China. The unique dying process of traditional clothing employed by these people has distinct national characteristics, a profound impact on the production and life of local people, and important research value. For this reason, it is important to investigate and document the dyeing plants and the traditional knowledge involved in the dyeing of Baku Yao traditional clothing. Methodology … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Author details 1 Guangxi Institute of Chinese Medicine & Pharmaceutical Science, Nanning 530022, China. 2 Guangxi Key Laboratory of Traditional Chinese Medicine Quality Standards, Nanning 530022, China. 3 Lushan Botanical Garden, Jiangxi Province and Chinese Academy of Sciences, Lushan 332900, China.…”
Section: Author Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Author details 1 Guangxi Institute of Chinese Medicine & Pharmaceutical Science, Nanning 530022, China. 2 Guangxi Key Laboratory of Traditional Chinese Medicine Quality Standards, Nanning 530022, China. 3 Lushan Botanical Garden, Jiangxi Province and Chinese Academy of Sciences, Lushan 332900, China.…”
Section: Author Contributionsmentioning
confidence: 99%
“…We were interested in examining how this transformation from traditional to modern culture changed their lifestyle over time. Our past research on Baiku Yao focused on plants used for various purposes, such as herbal medicine, foraging, dyeing, and veterinary medicine [1][2][3], and showed that Baiku Yao holds wealthy traditional knowledge about plants and their applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant-based dyeing systems are based on a big amount of traditional knowledge that provides insights on optimal processing conditions (Adeel et al, 2019). Multiple ethnological studies report that the use of plants for dyeing is rooted in the context of the territory and the tribal population in which the knowledge has developed (Example: Hu et al, 2022;Teron et al, 2012). However, this knowledge and application of the process are currently under threat due to the easy accessibility of synthetic dyes and issues related to acculturation (Teron et al, 2012).…”
Section: Traditional Knowledge and Modern Biotechnologiesmentioning
confidence: 99%
“…[ 1 , 2 , 3 , 4 ]. Species used for traditional dyeing and the techniques employed have been recorded in some areas of the world [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%